The G332 molecular cloud ring: I. Morphology and physical characteristics. Issue 2 (2nd January 2019) - Romano, Domenico; Burton, Michael G; Ashley, Michael C B; Molinari, Sergio; Rebolledo, David; Braiding, Catherine; Schisano, Eugenio
Abstract: We present a morphological and physical analysis of a giant molecular cloud (GMC) using the carbon monoxide isotopologues ( 12 CO, 13 CO, C 18 O 3 P 2 → 3 P 1 ) survey of the Galactic Plane ( Mopra CO Southern Galactic Plane Survey ), supplemented with neutral carbon maps from the HEAT telescope in Antarctica. The GMC structure (hereinafter the ring ) covers the sky region 332° < ℓ < 333° and $\mathit {b}$  = ±0.5° (hereinafter the G332 region ). The mass of the ring and its distance are determined to be ${\sim }2\times 10^{5}\, \mathrm{M}_{\odot}$ and ${\sim }3.7\rm \, kpc$ from the Sun, respectively. The dark molecular gas fraction – estimated from the 13 CO and [C i ] lines – is ${\sim }17{{\ \rm per\ cent}}$ for a CO Tex between [10, $20\rm \, K$ ]. Comparing the [C i ] integrated intensity and N(H2 ) traced by 13 CO and 12 CO, we define an X$\mathrm{_{CI}^{809}}$ factor, analogous to the usual X co, through the [C i ] line. $X\mathrm{_{CI}^{809}}$ ranges between [1.8, 2.0] $\times 10^{21}\, \mathrm{cm}^{-2}\, \mathrm{K}^{-1}\, \mathrm{km}^{-1}\, \mathrm{s}$ . We examined local variation in X co and T ex across the cloud, and find in regions where the star formation activity is not in an advanced state, an increase in the mean and dispersion of the X co factor as the excitation temperature decreases. We present a catalogue of C 18 O clumps within the cloud, and report their physical characteristics. The star formation (SF) activity ongoing in the cloud shows a correlation with T ex, [C i ], and CO emissions, and anticorrelation with X co, suggesting a North–South spatial gradient in the SF activity. We propose a method to disentangle dust emission across the Galaxy, using H i and 13 CO data. We describe virtual reality and augmented reality data visualization techniques, which open new perspectives in the analysis of radio astronomy data.